The family Baetidae (Insecta: Ephemeroptera): synthesis and future - Abad, Gabriela Alejandra (2009)
The systematics of the Baetidae has been the subject of much attention during the last three decades, with descriptions of new species and genera as well as several generic revisions. The family now encompasses about 100 genera and 900 species which constitute one-quarter of the world's mayfly diversity. It is thus an opportune time to evaluate the pertinence of these works. The diversity of the Baetidae of the different realms is discussed with emphasis on the rate of endemism and biogeographic affinities. We have also tried to identify the geographical areas where we need more data. The Afrotropics and Neotropics possess the most diversified fauna with the highest degree of endemism. The faunas of the Palaearctic and Nearctic realms are better known but are less diversified especially at a generic level. Oriental and Australasian faunas are still poorly known but are expected to be diversified especially in the tropical regions.